Der modularisierte Mann: Eine Sozialtheorie der Männlichkeit - Böhnisch, Lothar (transcript, 2018)
In the "second modern age" masculinity is rejected yet demanded. Many men try to deal with this issue pragmatically. In a society that unitizes conflicts – i.e. differentiates them by turning them into single, flexible components – instead of depoliticizing them, the "new man" is also a unitized man. He will act strategically in various areas of his life and refers to the different parts of his identity, some of which contradict each other – the modules of his masculinity. Lothar Böhnisch presents an integrated theoretical approach that makes manhood and what it means to be a man the subject of discussion in a structural context, putting psychoanalytical as well as social dimensions in relation with each other while informing about gender theory and social theory in an innovative way. This new approach to men's studies in German language suggests linking them to other sociological disciplines that deal with men's studies.